Unravelling the allosteric binding mode of αD-VxXXB at nicotinic acetylcholine receptors - Ho, Thao NT; Abraham, Nikita; Lewis, Richard J. (Frontiers in Pharmacology, 2023)
alphaD-conotoxins are 11 kDa homodimers that potently inhibit nicotinic acetylcholine receptors (nAChRs) through a non-competitive (allosteric) mechanism. In this study, we describe the allosteric binding mode of the granulin-like C-terminal (CTD) of VxXXB bound to Lymnea stagnalis acetylcholine binding protein (Ls-AChBP), a soluble homologue of the extracellular ligand-binding domain of nAChRs. This co-crystal complex revealed a novel allosteric binding site for nAChR antagonists outside the C-loop that caps the orthosteric site defined by the nAChR agonist nicotine and the antagonist epibatidine. Mutational and docking studies on Ls-AChBP supported a two-site binding mode for full-length VxXXB, with the first CTD binding site located outside the C-loop as seen in the co-crystal complex, with a second CTD binding site located near the N-terminal end of the adjacent subunit of AChBP. These results provide new structural insight into a novel allosteric mechanism of nAChR inhibition and define the cooperative binding mode of the N-terminal domain linked granulin core domains of alphaD-conotoxins.